War Economy: The Untold Logistics of South Sulawesi’s DI/TII Rebellion (1950-1965) - Ahmad Subair (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study reveals that the resilience of the DI/TII Movement in South Sulawesi (1950-1965) was not solely based on ideology, but on an independent war economy system. At the core of this system was control over copra commodities, which were exchanged for weapons through a regional black market smuggling network that reached Tawao and Singapore. A special agency, the Contact Post (CP), served as the logistical and fiscal operator that regulated trade, taxation, and currency within the movement's de facto territory. Another crucial finding is the symbiotic relationship between this network and individuals within the state apparatus (see Andi Sose's archives about the Army's copra foundation 1956). However, the system eventually collapsed due to a combination of logistical blockades by the Regional Military Command, internal divisions, and acute weapon shortages. This study concludes that in protracted conflicts, sovereignty over logistics and economic supply chains is often a more vital determinant than ideological factors alone.